The availability and accessibility of vertical file collections in Jamaican libraries - Newman, Dunstan (2021)
Small island developing states are often characterized by weak local publishing industries and infrastructure, which leads to the unavailability of locally relevant publications. Given this reality, the vertical file collections are therefore an important source of indigenous information. In view of this, the authors sought to determine to what extent are vertical files existent and prevalent in Jamaican libraries especially in an age of increasing reliance on electronic resources. The authors also examine how Jamaican libraries make these vertical files accessible to the public. To achieve this, both a survey and a comparative study of vertical files in selected library and information service environments in Jamaica were undertaken. The results indicate that vertical files exist in a variety of environments. However, more can be done in Jamaican libraries to improve the accessibility of vertical file collections to users. There is need for closer attention to be paid to vertical files in Jamaica and their promotion, as these collections are very valuable sources of local information not yet documented by local publishers.